Growth path tools for young and developing farmers : farm task mapping - Leppälä, Jarkko; Markkanen, Jukka; Vasiliauskas, Gediminas (Vytautas Magnus University, 2024)
This study is to develop techniques for business engineering on farms. Changes outside the farms are reflected in the agricultural sector placing new demands for the farm managers career paths and expertise. To have success in farm business a young farmer needs to find strategies adapting these changes to the operational tasks of the farm. In adaptation, it is important to see the possibilities of development during the farm’s life cycle. Agricultural entrepreneur usually faces the farm activities as a holistic system. The sustainability of the farm business depends on the conditions of the production processes and the agricultural entrepreneur’s ability to operate at different stages of his or her career path. In agriculture change is regulated by its own legislation, market regulation, customer requirements, traditions, and work culture, which must be taken into account in maintaining the vitality of the farm system. In Finland, the AgriHubi network offers a new channel for agriculture industry stakeholders to provide tools for the development of agricultural entrepreneurs’ management skills and career growth path. One of the results of this project is the identification of farm entrepreneurs’ development areas with the help of the farm task map tool. The task mapping method is based on mapping the important elements of the company.
Keywords: farm safety; agriculture machine injury accidents; safety communication